2020
DOI: 10.1167/tvst.9.12.28
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Indigenous Australian Children

Abstract: This study aimed to examine the choroidal thickness profiles in visually normal Australian Indigenous children, given the important role of the choroid in refractive error and a range of ocular diseases. Methods: Choroidal thickness was assessed across the central 5 mm macular region using enhanced depth imaging spectral domain optical coherence tomography, in 250 children enrolled in an elementary school and a secondary school in rural Queensland, Australia. One hundred (40%) of these children identified as I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
2
5
1
Order By: Relevance
“…We nevertheless managed to find a significant age-related change in ChT with the included study sample. Moreover, our current sample size remains larger than or similar to those of many previous longitudinal 8 , 9 , 11 , 55 or cross-sectional 7 , 10 , 15 , 17 , 20 , 21 studies (approximately 100–200) that have described age-related variations in the choroidal thickness. Although there was a statistically significant age difference between participants included and excluded from the analysis, the age difference was small (approximately 0.2 years or 2.4 months).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We nevertheless managed to find a significant age-related change in ChT with the included study sample. Moreover, our current sample size remains larger than or similar to those of many previous longitudinal 8 , 9 , 11 , 55 or cross-sectional 7 , 10 , 15 , 17 , 20 , 21 studies (approximately 100–200) that have described age-related variations in the choroidal thickness. Although there was a statistically significant age difference between participants included and excluded from the analysis, the age difference was small (approximately 0.2 years or 2.4 months).…”
Section: Discussionsupporting
confidence: 51%
“…In younger 6 12 , 14 16 or older 17 20 age groups, ChT and its variation with age have been profiled by several studies. Longitudinal 8 , 9 and cross-sectional studies 6 , 7 , 14 , 15 , 21 in Western populations have suggested that the ChT tends to increase during childhood, with a slower rate of thickening noted with faster axial elongation. 8 , 9 On the other hand, studies in East Asia, which has a larger proportion of myopes, have argued that the ChT tends to decrease or does not vary with age during childhood.…”
mentioning
confidence: 99%
“…All measurements were conducted between 9 am and 3 pm . Results from the analyses of refractive error, stereoacuity, color vision, ocular alignment, accommodation and vergence function, ocular biometry, and macular OCT measures in this population have been reported previously 18–21 …”
Section: Methodsmentioning
confidence: 52%
“…Results from the analyses of refractive error, stereoacuity, color vision, ocular alignment, accommodation and vergence function, ocular biometry, and macular OCT measures in this population have been reported previously. [18][19][20][21] The Heidelberg Spectralis SD-OCT uses a superluminescent diode with a central wavelength of 870 nm, capturing 40,000 A-scans per second, to generate images with a digital axial resolution of 3.9 µm and transverse resolution of ~5.8 µm. With the left eye occluded, 2 highresolution (1024 A-scans) ONH scans were performed, each consisting of a horizontal and a vertical 20-degree long scan, centered on the middle of the ONH to determine the vertical and horizontal dimensions of the ONH and neuroretinal rim and to measure the thickness of the peripapillary RNFL.…”
Section: Methodsmentioning
confidence: 99%
“…2 Currently, some studies have investigated macular choroidal thickness and the relationships with certain clinical parameters based on different ethnicities and clinical schemes using OCTs. 3,4 However, few previous studies underwent comprehensive surveys regarding the relationship between macular choroidal thickness and clinical factors in Asian people with normal eyes, and no study has investigated that in the healthy Taiwanese population, which should be further studied for providing important regional The results of the analysis turned out that the mean choroidal thickness was 248.3 ± 83.8 μm. Pearson's correlation revealed that age (r = À0.179, p = 0.002) and SERE (r = 0.120, p = 0.043) had a significant correlation with the macular choroidal thickness; however, gender (r = 0.032, p = 0.582) and AL (r = À0.049, p = 0.403) were not related to macular choroidal thickness after the analysis.…”
mentioning
confidence: 99%